Spinal versus General Anaesthesia for Laparoscopic Gynaecological Procedures: A Comparative Study of Haemodynamic Changes and Side Effects - Masum, Abdullah; Islam, Md Saiful; Haque, Mozibul; Ahmed, Masud; Kalam, Farzana (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Laparoscopic gynaecological procedures are conventionally done under general anaesthesia. Spinal anaesthesia is usually preferred only in patients where general anaesthesia is contraindicated. For laparoscopic gynaecological procedures sub arachnoid block is gaining popularity day by day as it is a good alternative to GA. Objective: To compare haemodynamic changes and side effects between subarachnoid block (SAB) and general anaesthesia (GA) for lower abdominal laparoscopic gynaecological procedures. Materials and Methods: A total number of sixty female patients were considered and divided equally into two groups as per American Society of Anesthesiologists (ASA) grade I and II. All patients underwent short duration (<1hr) laparoscopic gynaecological procedures. Group-I patients received lumber SAB and group-II patients received standard general anaesthesia using Propofol, Halothane and Fentanyl. Peri-operative heart rate, blood pressure, Electro-cardiogram (ECG) and Saturation of Oxygen (SPO2) were monitored. Any intra operative and post operative side effects were also recorded and managed. Results: Intra operative and post operative heart rate, systolic and diastolic blood pressure were significantly higher (P<0.05) in group-II. Preoperative, per operative and post operative mean blood pressure (MBP) were also significantly higher (P<0.05) in group-II. During intraoperative period, the side effects in group-I were mainly discomfort and shoulder tip/neck pain and in group-II were hypertension and arrhythmia. Postoperative side effects were mainly postoperative nausea and vomiting (PONV). Conclusion: Spinal anaesthesia using mixture of bupivacaine and fentanyl can be used as a safe alternative to GA for short duration gynaecological laparoscopic procedures with minimum haemodynamic alterations and reduced post operative side effects. To alleviate shoulder tip/neck pain or discomfort patient needs supplementary sedation and analgesia. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 20-24